1989
DOI: 10.1109/58.19177
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of homomorphic processing for ultrasonic grain signal characterization

Abstract: A model for the grain signal is presented, which includes the effect of frequency-dependent scattering and attenuation. This model predicts that the expected frequency increases with scattering and decreases with attenuation. Homomorphic processing was used for spectral smoothing, and the selection of parameters for optimal performance was examined. Experimental results are presented that show both the upward shift in the expected frequency with grain boundary scattering and the downward shift with attenuation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(35 citation statements)
references
References 19 publications
0
34
0
Order By: Relevance
“…Elsley et al [10] have reported that the flaw spectrum peaks at a frequency lower than that of the trans duc er spectrum. The frequency dependence of the scattering coefficient in the Rayleigh scattering region has been studied by Saniie et al [11]. The results show that the intensity of the backscattered components Is targer at high frequencies, which indicates that grain noise due to scattering will be greater at higher frequencies.…”
Section: Theoretical Analysismentioning
confidence: 85%
“…Elsley et al [10] have reported that the flaw spectrum peaks at a frequency lower than that of the trans duc er spectrum. The frequency dependence of the scattering coefficient in the Rayleigh scattering region has been studied by Saniie et al [11]. The results show that the intensity of the backscattered components Is targer at high frequencies, which indicates that grain noise due to scattering will be greater at higher frequencies.…”
Section: Theoretical Analysismentioning
confidence: 85%
“…Using the mercury intrusion method, we verified that, at 10 MHz, E[D]/ varied between 0.026 and 0.071 for the di↵erent types of cement paste considered, where is the wavelength and D is the mean grain size. Therefore, we are working in the Rayleigh region [23], and we have a moderate, but su cient, amount of grain noise. When the frequency increases, it produces an attenuation that is too large; when the frequency decreases, it reduces the level of GN (the ultrasound pulse propagated better, but there were no echoes from the inner microstructure).…”
Section: Application To the Characterization Of Cement Pastesmentioning
confidence: 99%
“…(c) (dashed line) using a 28ps (approximately equivalent to the duration of a single echo governed by the characteristic of the transducer) shortpass lifter. Note that this duration for the shortpass lifter is chosen to provide sufficient smoothing [2]. The scattering function, S(f), can be found by the ratios of the spectrums of the grain echoes ((5)) and the back surface echo ( ( 4 ) ) , Rg(j)/Rb(f), which is displayed in Fig.…”
Section: Iw)i X I a (~) I I W ) I (4)mentioning
confidence: 99%